2001
DOI: 10.1590/s0036-46652001000400012
|View full text |Cite
|
Sign up to set email alerts
|

Entomophthoramycosis by Conidiobolus coronatus. Report of a case successfully treated with the combination of itraconazole and fluconazole

Abstract: Rhinoentomophthoramycosis caused by Conidiobolus coronatus in a 61-year old woman was unsuccessfully treated during 8 years with all the antifungals available in the Brazilian market, including potassium iodide for 1 month, sulfamethoxazole plus trimethoprim for 2 months, amphotericin B, total dose of 1130 mg, cetoconazole, 400 mg/day for 6 months, fluconazole, 200 mg/day, for at least 2 months and, itraconazole, 400 mg/day for 2 months, followed by 200 mg/day for 4 more months. Complete clinical and mycologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 7 publications
0
24
0
5
Order By: Relevance
“…In humans and other animals, potassium iodide has been the traditional and effective treatment against Conidiobolus infections (Owens et al 1985). Several other drugs, such as: amphotericin B, cotrimoxazole, ketoconazole, itraconazole and fluconazole have been also effective in humans and animals with the disease (Moraes et al 1994, Valle et al 2001, Grooters 2003. Interestingly, in one case of rhinofacial form of the disease, the treatment with iodides of one affected animal with early clinical signs of the disease was partially successfully, suggesting that in the early form of the disease the treatment could be successful if it is initiated immediately after the observation of the first clinical signs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans and other animals, potassium iodide has been the traditional and effective treatment against Conidiobolus infections (Owens et al 1985). Several other drugs, such as: amphotericin B, cotrimoxazole, ketoconazole, itraconazole and fluconazole have been also effective in humans and animals with the disease (Moraes et al 1994, Valle et al 2001, Grooters 2003. Interestingly, in one case of rhinofacial form of the disease, the treatment with iodides of one affected animal with early clinical signs of the disease was partially successfully, suggesting that in the early form of the disease the treatment could be successful if it is initiated immediately after the observation of the first clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of these species in pure culture from nostril, and facial areas, confirmed the predilection of Conidiobolus spp. for this type of tissues (Bridges et al 1962, Miller & Campbell 1982, Mendoza & Alfaro 1985, Humber et al 1989, Carrigan et al 1992, Valle et al 2001. Although Basidiobolus ranarum can also cause eosinophilic subcutaneous infections in apparently healthy individuals, this zygomycetous fungus is more common on limbs and anatomical areas other than the face (Miller & Pott 1980, Owens et al 1985, Greene et al 2002, Grooters 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chandler et al (2000) demonstrated that a number of isolates from these genera infect mites; however, only Conidiobolus coronatus (Constantin) Batko was reported to be isolated from a tick species, Ixodes ricinus L. This fungus is found in soil and decaying plant debris and is known to be pathogenic to a number of insect species (Kedra and Bogus 2006), but it is known to cause entomophytoramycosis (formation of tumours) in humans (Valle et al 2001). The mould Rhizopus thailandensis (Zygomycete) has demonstrated experimental pathogenicity to Rhipicephalus sanguineus Latreille; however, under field conditions the performance was poor (Casasolas-Oliver 1991).…”
Section: Fungal Speciesmentioning
confidence: 99%
“…Different azoles, amphotericin B, and flucytosine have been shown to be effective in vitro [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and a number of azoles as well as amphotericin B, potassium iodide, and sulfamethoxazole plus trimethoprime have been described to have a beneficial clinical effect in some patients [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%